2014
DOI: 10.1111/evj.12328
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship between anti‐Müllerian hormone, ovarian follicular populations and age in mares

Abstract: Our findings indicate that the relationship between AMH and AFC varies across age groups, and concentrations of AMH might be a better reflection of reproductive age than calendar age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 39 publications
7
45
1
4
Order By: Relevance
“…This result supports a previous study showing that peripheral AMH concentrations are primarily associated with the number of follicles between 6 and 20 mm [3]. This result supports a previous study showing that peripheral AMH concentrations are primarily associated with the number of follicles between 6 and 20 mm [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result supports a previous study showing that peripheral AMH concentrations are primarily associated with the number of follicles between 6 and 20 mm [3]. This result supports a previous study showing that peripheral AMH concentrations are primarily associated with the number of follicles between 6 and 20 mm [3].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study, however, revealed that increasing oestradiol concentrations reduces the expression of AMH via oestrogen receptor beta (ESR2) [15]. A single blood sample was collected 6 days after ovulation for determination of plasma AMH concentrations, and AFC was determined as previously described [3]. Follicle-stimulating hormone acting through the FSHR also plays a role in the regulation of AMH; however, it is unclear whether FSH has a stimulatory or inhibitory effect on the expression of AMH [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who begin their life with a low antral follicle count/ovarian reserve tend to experience low AMH levels relative to other women of similar age. This relationship is observed in multiple species including mice, cows, goats and horses (Kevenaar et al 2006, Monniaux et al 2012, Batista et al 2014, Claes et al 2015.…”
Section: Anti-müllerian Hormone Expression In the Ovarymentioning
confidence: 92%
“…Anti-M€ ullerian hormone, ovarian follicular populations and age [7] Mares do not have a menopause as such, but fertility declines with age for several, poorly understood reasons. One contributing factor is undoubtedly irregular cycling manifested by prolonged follicular phases and leading ultimately to a cessation of ovulation.…”
Section: Inflammatory Mechanisms Of Endometritis [1]mentioning
confidence: 99%